2019
DOI: 10.1002/adma.201808197
|View full text |Cite
|
Sign up to set email alerts
|

Electron Transfer in Nanoscale Contact Electrification: Effect of Temperature in the Metal–Dielectric Case

Abstract: The phenomenon of contact electrification (CE) has been known for thousands of years, but the nature of the charge carriers and their transfer mechanisms are still under debate. Here, the CE and triboelectric charging process are studied for a metal–dielectric case at different thermal conditions by using atomic force microscopy and Kelvin probe force microscopy. The charge transfer process at the nanoscale is found to follow the modified thermionic‐emission model. In particular, the focus here is on the effec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
155
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
5

Relationship

4
1

Authors

Journals

citations
Cited by 198 publications
(175 citation statements)
references
References 32 publications
6
155
0
Order By: Relevance
“…The OEC model was further tested when a temperature difference was established between the tip and sample. In the experiments, the sample temperature was maintained at 313 K and tip temperature were varied from 313 to 433 K (the details for the temperature control were described in our previous studies) . The effects of the temperature difference on the phase shift of the tapping tip are shown in Figure S3 (Supporting Information).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…The OEC model was further tested when a temperature difference was established between the tip and sample. In the experiments, the sample temperature was maintained at 313 K and tip temperature were varied from 313 to 433 K (the details for the temperature control were described in our previous studies) . The effects of the temperature difference on the phase shift of the tapping tip are shown in Figure S3 (Supporting Information).…”
Section: Resultsmentioning
confidence: 99%
“…The conductive tip used here was Multi75E‐G (BudgetSensors, Bulgaria; Pt‐coated; tip radius: 25 nm; spring constant: 3 Nm −1 ). In the temperature effect experiments, the sample temperature and the tip temperature were controlled by the sample heater and the tip heater, respectively (the details of the temperature experiments were described somewhere else) . In the tapping mode charging experiments, the interaction region between the tip and sample was controlled by setting the free amplitude and set tapping amplitude of the tip in the scanning.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Also, although the Q SC rapidly decayed at higher test temperatures for the contact–separation mode Ti–SiO 2 TENGs, the sliding mode TENG was capable of generating even a small amount of transferred charge (0.05 nC) before decay took over at the highest tested temperature (563 K). In addition to Q SC , surface charge density is also a satisfactory variable in investigating temperature effects on TENGs, and a recent study using and tapping mode AFM has found that triboelectric charge decay follows the thermionic emission model at nanoscale . It would be of great interest to continue this line of research by using contact scanning mode AFM to mirror a sliding mode TENG.…”
Section: Design and Performance Of The Sliding Mode Ti–sio2 Tengmentioning
confidence: 99%